Sosiologi Pendidikan Dasar di Desa Padat Penduduk: Modal Sosial, Identitas, dan Reproduksi Sosial - Lidhah Sekar Mulatsih; Muh. Hanif (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Basic education in densely populated rural areas is often associated with limited educational opportunities and the persistence of social inequality. However, the interaction between community social capital, student identity formation, and social reproduction within the school environment remains an important issue to be explored. This study aims to examine how these three dimensions operate simultaneously at SDN 1 Kedungwringin, Patikraja District, Banyumas Regency, Central Java. The research employed a qualitative single-case study approach. Data were collected through participant observation, in-depth interviews with students, homeroom teachers, parents, and community leaders, as well as analysis of school documents from the 2024/2025 academic year. The findings reveal that community social capital, manifested through networks of trust, mutual support, and collective concern for education, significantly contributes to sustaining educational participation, as reflected in a school participation rate of 98 percent and a zero dropout rate. Student identity is predominantly shaped through Islamic values and local cultural achievements, strengthening their sense of belonging and self-confidence. Furthermore, the school performs a dual function by reproducing certain social differences rooted in family economic conditions while simultaneously providing opportunities for social mobility through character education and local wisdom programs. The study implies that rural spatial conditions do not necessarily hinder educational development and that strengthening community social capital is a strategic factor in enhancing the emancipatory role of primary education institutions in promoting equitable educational opportunities and social advancement.